Virtual reality boxing: impact of gaze-contingent blur on elite boxers performance and gaze behavior - Limballe, Annabelle; Kulpa, Richard; Verhulst, Eulalie; Ledouit, Simon; Bennett, Simon J. (Frontiers in Sports and Active Living, 2024)
It is essential in combat sports such as boxing for athletes to perceive the relevant visual information that enables them to anticipate and respond to their opponent's attacking and defensive moves. Here, we used virtual reality (VR), which enables standardization and reproducibility while maintaining perception-action coupling, to assess the influence of a gaze-contingent blur on the visual processes that underpin these boxing behaviours. Eleven elite French boxers were placed in an immersive and adaptive first-person VR environment where they had to avoid by dodging one or two punches, and then counterattack to strike their opponent. The VR boxing task was performed in a central blur, peripheral blur and control condition. The results showed that elite boxers outcome performance was resilient to blur, irrespective of its location in the visual field. However, there was an effect of blur on the eye gaze data, with participants spending less time looking at the left hand and plexus, and more time looking at the head and areas other than the boxer, in the peripheral blur condition. Overall, then, our study contributes to growing evidence that performance in dynamic interceptive sports can be maintained when the visual stimulus is artificially blurred. In future work, it will be relevant to consider whether VR training with a gaze-contingent blur can facilitate learning, transfer, and/or reintroduction after injury, to a real boxing situation.